Addressing victimization to enable societal participation in flexible assertive community treatment: A process evaluation of the implementation of a new intervention - Albers, Wendy M. M.; Nijssen, Yolanda A. M.; Roeg, Diana P. K.; van Weeghel, Jaap; Bongers, Inge M. B. (Frontiers in Psychiatry, 2022)
Background: Individuals with severe mental illness experience more victimization and discrimination than other persons in the community. Effective rehabilitation and recovery-oriented care interventions aimed at addressing this issue are lacking. We therefore developed a victimization-informed intervention (accompanied by a training module for professionals) called the Victoria intervention. The purpose of the present study was to understand the trial effects by examining the implementation process and the factors that influenced it. Methods: A process evaluation was conducted using a mixed-methods design. During the professionals’ intervision sessions, we used observations to understand the learning processes (n = 25). Subsequently, we studied the use of the intervention in practice through structured questionnaires (n = 215) and semi-structured interviews (n = 34) with clients and professionals. We used descriptive and inferential statistics for the quantitative data and the framework method for the analyses of the qualitative data. Results: The observations showed that the trainings were well received. The professionals shared the urgency of paying attention to victimization and discrimination and its harmful effects on participation. They also found the intervention steps to be logical and the intervention protocol easy to use. Nevertheless, they mentioned in the interviews that they had experienced difficulties initiating a conversation about victimization, and if they started one, they did not always follow the steps of the intervention as intended. Few clients said that victimization was placed on the agenda, though those who had discussed victimization with their caregivers expressed their appreciation in the interviews; they felt acknowledged and supported. Discussion: The findings indicate that the intervention was considered helpful in raising awareness and the acknowledgment of victimization. However, professionals remain reluctant to talk about the subject, and the results show they need more practical training in this regard. This process evaluation has an important added value in that it helps us to understand the results of the effect evaluation of the intervention. The findings will facilitate the development and implementation of interventions that address clients’ victimization experiences in community mental health care settings and subsequently enable their participation in society.